The Judicial Role of the Kurdistan Region's Shura Council in Establishing the Principle of Equality in the Scope of Public Employment (An Analytical Study) - jangeer, فارس; mohammed , زیرك (Zanco Journal of Law and Politics گۆڤاری زانكۆ بۆ یاساو رامیاری, 2025)
The principle of equality is one of the fundamental principles that guarantee individual rights in any democratic society. It serves as the cornerstone of a legal system that ensures justice and equal opportunities for all citizens. This principle is also a key foundation of any administrative system, ensuring fairness among all individuals. In the realm of public employment, equality holds particular significance, requiring that all employees be granted equal opportunities in employment rights, task distribution, and fair treatment without discrimination. Judicial oversight institutions, such as the Shura Council of the Kurdistan Region of Iraq, play a crucial role in upholding and safeguarding this principle against violations within administrative practices. They also ensure the application of legal equality among individuals in all fields, particularly in public employment. The most effective guarantee for strengthening the principle of equality among employees in terms of rights and duties lies in reinforcing judicial oversight over decisions affecting employees, especially concerning employment rights. Effective judicial oversight ensures that decisions related to promotions, bonuses, employment benefits, task distribution, and treatment are made by the principles of justice and equality.